The Impact of Problem-Based and Culturally Responsive Teaching on Civic Learning Achievement in Primary School Students: An Experimental Study - Purnamasari, Ratih; Muhammad Arfan Fadiah; Mursida Alfitra; Siti Farah Delina; Sumayanti (Jurnal Elementaria Edukasia, 2025)
Pancasila education in elementary schools still focuses on the cognitive aspect and has not yet fully succeeded in shaping students' behavior in accordance with Pancasila values. This reflects the need for a more contextual approach so that students can internalize these values through a love for local culture and wisdom. This study aims to examine the effect of applying the Problem-Based Learning (PBL) model combined with a Culturally Responsive Teaching (CRT) approach on the civic learning achievement of fifth-grade students at SDN Panaragan 1, Bogor City. The study employed a quasi-experimental method using a Nonequivalent Control Group Design. The subjects consisted of two groups: class VA consisting of 33 students as the experimental group receiving PBL integrated with CRT, and class VB consisting of 33 students as the control group taught using conventional methods. Data were collected through a 25-item multiple-choice test that had been previously validated and tested for reliability. The results showed that the average N-Gain score in the experimental group was 77, while the control group scored 69. A t-test revealed that the t_calculated value (2.68) was greater than the t_table value (1.99773), indicating a significant effect of integrating PBL and CRT on students' civic learning outcomes. Based on these findings, it can be concluded that the use of the PBL model combined with the CRT approach effectively enhances students' enthusiasm, participation, interest, and learning achievement in Pancasila education. Therefore, it is recommended that this integration of PBL and CRT be implemented in other classes and schools.